The unbeatable Squirrel Girl : squirrel meets world - Hale, Shannon; Hale, Dean, 1972- (Marvel, 2017)
After Doreen uses her extraordinary powers to stop a group of troublemakers, she becomes a full-fledged superhero called Squirrel Girl.